Healthy Diversity? The Politics of Managing Emotions in an Ethnically Diverse Hospital Workforce. (3rd July 2020) - Lee, Sandy; Collins, Francis L.; Simon-Kumar, Rachel
ABSTRACT: Emotions are increasingly incorporated into organisational diversity management initiatives to address some of the challenges said to arise from workforce diversity. Yet few studies have looked at the impact that this emphasis on managing emotions has on minority group struggles for equality, inclusion and justice. We examine this issue in a hospital workplace within a District Health Board located in the bicultural, multi-ethnic and settler colonial context of Aotearoa / New Zealand. Through analysis of diversity training documents and interviews with senior-level managers, we found that the use of emotionality individualised responsibility for inclusive diversity to healthcare workers and maintained the privileged emotions of the white majority. This obscured the structural issues that (re)produce exclusion and inequities.